Research Progress on the Impact of Post-Rain Sprouting and Germination on Wheat Yield and Quality - Feng, Simin; Yang, Ke; Gao, Shiqian (Scientific Journal of Technology, 2025)
During the wheat harvesting period, extreme weather events have frequently occurred, with an abundance of rainy days significantly impacting crop production. Following rainfall, sprouting and germination in wheat not only alter its external appearance but also lead to substantial changes in its intrinsic quality. This paper reviews the variations in yield, nutritional quality indicators, and processing quality metrics of sprouted and germinated wheat. Additionally, it explores new approaches for utilizing sprouted and germinated wheat.